Efficacy of reduced osmolarity oral rehydration solution, rice ... based oral rehydration solution, and standard WHO oral rehydration solution in children with acute diarrhea - a randomized open trial - Thermiany Anggri Sundari; Soetjiningsih Soetjiningsih; Sri Supar Yati Soenarto; I P. G. Karyana (Indonesian Pediatric Society, 2009)
Background The composition of the WHO's standard oral rehydration solution (ORS) is similar to that of choleric stool. Currently, there are questions about whether the composition is acceptable for treating dehydration caused by diarrhea. Efforts are being made to try and improve the WHO ORS, e.g., to decrease the solution osmolarity to avoid hypertonic side effects.lt is acknowledged that if glucose is used in ORS, the sodium will go through enterocytes and glucose will tum into an absolute substance for the formula. Glucose is less affordable and not widely produced in developing countries, hence researchers are currently exploring substitutes such as rice flour.Objective To compare the efficacy of reduced osmolarity ORS,rice-based ORS and the WHO standard ORS among childrenwith acute diarrhea.Methods A randomized open trial was conducted in children aged6-59 months old admitted for acute diarrhea. One-way AN OVAwas used to compare the three different types of ORS given.Results The mean duration of diarrhea was significantly lower inthe group treated with reduced osmolarity ORS (52.66 h, 95%CI 4 7.13 to 58.18) and rice-based ORS (54.66 h, 95% CI 4 7.97to 61.34) compared to the group treated with the WHO standardORS (67.34 h, 95% CI 61.50 to 73.18). Multivariate analysisshows that intervention had a significant effect on reducing theduration of diarrhea.Conclusions Reduced osmolarity ORS and rice-based ORSsignificantly lower the mean duration of children with acutediarrhea compared with the group treated with the WHO standardORS.